2019
DOI: 10.1021/acs.oprd.9b00195
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Catalyzed Couplings of Heteroaryl Primary Amines and (Hetero)aryl Bromides with 6-Hydroxypicolinamide Ligands

Abstract: A family of 6-hydroxypicolinamide ligands have been identified as effective supporting ligands for Cu-catalyzed couplings of heteroaryl bromides and chlorides with heteroaryl primary amines. The C−N couplings are carried out at 80−120 °C in DMSO or sulfolane using K 2 CO 3 or K 3 PO 4 as the base with 2−10 mol % CuI and supporting ligand. The strength of the base was found to have an impact on the chemoselectivity and rate. The use of K 2 CO 3 as the base enabled selective C−N coupling of aryl bromides over ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…The resulting slurry was filtered to isolate 6 as an off-white solid, which was dried in a vacuum oven at 50 °C to provide the product (13.8 g, 79% yield). Characterization data were consistent with those reported in the literature …”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…The resulting slurry was filtered to isolate 6 as an off-white solid, which was dried in a vacuum oven at 50 °C to provide the product (13.8 g, 79% yield). Characterization data were consistent with those reported in the literature …”
Section: Methodssupporting
confidence: 90%
“…In a second example, a family of 6-hydroxypicolinamide ligands were synthesized and evaluated for the development of Cu-catalyzed C–N coupling methodology . (Figure ) Through this work, ligand 6 emerged as optimal for C–N couplings of heterocyclic amines.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We started by evaluating a total of >40 ligands (consisting of mainly amines and amides); however, many yielded very low conversion. Nevertheless, we found that using ammonium hydroxide ( 6 ) along with sterically encumbered amide-derived ligands developed by either Ma , or Singer was successful in furnishing good selectivity for the monoarylated product. Unfortunately, these noncommercial ligands were the only promising leads, and we ultimately decided to pursue the use of an ammonia surrogate ( vide infra ).…”
Section: Resultsmentioning
confidence: 96%
“…Compounds containing an NH‐bridge were accessed via nitration of pyrazole 12 , followed by iron‐mediated reduction to afford aminopyrazole 22 (Scheme 5). A Buchwald‐Hartwig coupling of this intermediate with bromobenzenes provided a library of NH‐bridged analogues 23 [14] . Alkylation with iodomethane afforded the N ‐methyl derivatives 24 .…”
Section: Resultsmentioning
confidence: 99%